Stroke of luck - Daniels, B. J (Sterling's Montana, 2019)
The Sterling Ranch<U+2019>s season opening isn<U+2019>t going so smoothly. With the ranch<U+2019>s lodge full of guests and a Montana blizzard threatening, Will Sterling needs help<U+2014>and he needs it fast. So when his childhood friend Poppy Carmichael agrees to lend a hand, he<U+2019>s grateful for a second chance<U+2026>and more enticed by the woman she<U+2019>s become than he cares to admit. For Poppy, it was supposed to be a retreat full of horse rides and hoedowns<U+2014>with a side of showing Will what he<U+2019>s been missing all these years. But as the snow deepens outside, the guests<U+2019> suspicion and mistrust turn sinister inside, catching Will and Poppy in the crosshairs. Weathering the storm in each other<U+2019>s arms is all too easy for Will and Poppy, but will a confrontation with a killer mean their reunion is short-lived?